Fuzzy Disturbance Observer-Based Fixed-Time Attitude Control for Hypersonic Morphing Vehicles - Zhang, Hao; Wang, Peng; Tang, Guojian; Bao, Weimin (IEEE transactions on aerospace and electronic systems, 2024)
This article develops a fuzzy disturbance observer-based fixed-time control technique to solve the attitude-tracking problems for hypersonic morphing vehicles (HMVs). According to the dynamic model of HMVs, the control-oriented model is established to simplify the design procedure. Fuzzy fixed-time disturbance observers are proposed for high-precision and fast disturbance estimation. The attitude controller is developed based on multivariable sliding mode control and fixed-time stability technique. Compared with the conventional fixed-time control methods, this article adopts variable exponent coefficients to achieve fixed-time stability. The controller will be obtained without lengthy inner and outer loop design procedures. The closed-loop stability is proved via Lyapunov synthesis. Finally, several scenarios are designed to assess performance.